Aiming high : new development goals could spur progress toward better-quality life around the world - Kenny, Charles (2015)
Looks at progress made to achieve the Millennium Development Goals (MDGs) and examines the potential for continued progress over the next fifteen years for the Sustainable Development Goals (SDGs) to be agreed at the United Nations in 2015.